Virus-Virus Saluran Pernapasan yang Paling Banyak Ditemukan pada Anak Balita Pasien SARI (Severe Acute Respiratory Infections) - -, Widoretno; Saragih, Siti Mariani; Lokida, Dewi (Jurnal Biotek Medisiana Indonesia, 2012)
In children, 50% respiratory infection was caused by viruses. This research was aimed to identify type of viruses causing respiratory infection among SARI patients under five years old in several regions in Indonesia.Study design of this reserach was prospective study using survey and laboratory analysis. Data was being collected from SARI surveillance. There were 215 throat specimens from 350 children under five years old patients. Specimens were collected from March 2008 to December 2008. To detect viruses in the respiratory tract, this research used Multiplex Bead Array Assay technique.Among 215 specimens tested, 91 specimens (40.12%) were positive respiratory viruses. In children under 1 year old, Coxsakie and Enterovirus (8.72%) were two viruses that mostly detected. In children aged 2 to 3 years old, the virus that mostly found was Respiratory Syncytial virus. And in children aged 4 to 5 years old, Entero and Rhinovirus were mostly found (14.29%). Based on the distribution of respiratory viruses in hospital, there were two peaks shown in the graphs. Firstly, Entero and Rhinovirus were high in Kupang and DKI Jakarta. Secondly, Respiratory Syncytial virus was found high in Kupang, Semarang, and DKI Jakarta.Respiratory Syncytial, Coxsakie, Enterovirus, and Entero Rhinovirus were mostly identified in SARI Patients under five years old.Key word: respiratory viruses, SARI, children under five yearsÂ AbstrakPada anak-anak lima puluh persen penyebab infeksi saluran pernapasan adalah virus. Tujuan dari penelitian ini adalah unutk mengetahui jenis virus-virus pernapasan pada pasien balita rawat inap penderita SARI (Severe Acute Respiratory Infectiouns) di beberapa daerah di Indonesia. Desain penelitian prospektif dengan jenis studi survey dan studi laboratorium. Data berasal dari spesimen tersimpan surveilans SARI. Jumlah spesimen 215 usap tenggorok dari total 350 pasien balita. Spesimen dikumpulkan dari bulan Maret 2008-Desember 2008. Untuk mendeteksi virus-virus pada saluran pernapasan digunakan teknologi Multiplex Bead Array Assay. Diantara 215 spesimen, 91 spesimen (40,12 %) positif virus pernapasan. Pada anak dibawah 1 tahun, virus yang paling banyak ditemui adalah virus Coxsakie dan Entero Virus (8,72 %). Sedangkan pada anak usia 2-3 tahun virus yang paling banyak ditemukan adalah virus Respiratory Syncytial (17,24 %) dan pada anak usia 4-5 tahun virus yang paling banyak ditemukan adalah virus Entero dan Rhinovirus (14,29 %). Berdasarkan distribusi virus pernapasan di rumah sakit terlihat 2 puncak grafik yang menunjukkan tingginya virus Entero dan Rhino di Daerah Kupang dan DKI. Puncak grafik kedua yang menunjukkan tingginya virus Respiratory Syncytial di Daerah Kupang, Semarang dan DKI. Virus Respiratory Syncytial, Coxsakie dan entero virus serta Entero-Rhinovirus paling banyak ditemukan pada pasien balita SARI.Kata kunci: virus pernapasan, SARI, anak balita